Inactivation of Escherichia coli by Near-Ultraviolet Light and 8-Methoxypsoralen: Different Responses of Strains B/r and K-12 - Bridges, B. A. (1979)
A series of Escherichia coli K-12 AB1157 strains with normal and defective deoxyribonucleic acid repair capacity were more resistant to treatment with 8-methoxypsoralen (8-MOP) and near-ultraviolet light (NUV) than a comparable series of strains from the B/r WP2 family although sensitivities to 254-nm ultraviolet light were closely similar. The difference was most marked with strains deficient in both excision and postreplication repair (uvrA recA). The hypothesis that the internal level of 8-MOP was lower in K-12 than B/r uvrA recA derivatives was ruled out on the basis of fluorometric determinations of 8-MOP content and the similar inactivation curves for phage T3 treated intracellularly within the two strains. The demonstration of liquid holding recovery with AB2480 but not WP100 (both recA uvrA strains) and the somewhat greater resistance of the former strain to inactivation by captan revealed the presence in the K-12 strain of a deoxyribonucleic acid repair system independent of the recA(+) and uvrA(+) genes. The presence of this repair system did not, however, affect the survival of T3 phage treated with 8-MOP plus NUV and probably has a relatively small effect on survival of AB2480 under normal conditions. Experiments in which 8-MOP monoadducts were converted to cross-links by a second NUV exposure in the absence of 8-MOP indicated that the level of potentially cross-linkable monoadducts immediately after 8-MOP + NUV is about eightfold lower in K-12-than in B/r-derived strains. It is therefore suggested that the photoproduct yield in the former is well below that in the latter. In agreement with this is the observation that, during the first 10 min after treatment, deoxyribonucleic acid synthesis was just over five times more sensitive to inhibition by 8-MOP plus NUV in WP100 than in AB2480. We assume that 8-MOP in K-12 bacteria is hindered in some way from adsorbing to cellular (though not to phage T3) deoxyribonucleic acid. Consistent with this, 8-MOP has been shown to act as an inhibitor of a component of repair of 254-nm ultraviolet light damage in WP2 but not in AB1157.